2020
DOI: 10.2337/dc20-2989
|View full text |Cite
|
Sign up to set email alerts
|

Association and Familial Coaggregation of Type 1 Diabetes and Eating Disorders: A Register-Based Cohort Study in Denmark and Sweden

Abstract: To ascertain the association and coaggregation of eating disorders and childhoodonset type 1 diabetes in families. RESEARCH DESIGN AND METHODSUsing population samples from national registers in Sweden (n 5 2,517,277) and Demark (n 5 1,825,920), we investigated the within-individual association between type 1 diabetes and eating disorders and their familial coaggregation among full siblings, half siblings, full cousins, and half cousins. On the basis of clinical diagnoses, we classified eating disorders into an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 41 publications
0
11
0
1
Order By: Relevance
“…This is especially relevant as binge-eating behaviours have been shown to worsen metabolic markers, including glycemic control 127 . Type 1 diabetes (T1D) as well as other autoimmune associated disorders were also more common in individuals with BED than referent controls 128 . In two pilot studies, 23% 129 to 28% 130 of people with nonalcoholic fatty liver disease (NAFLD) screened positive for BED, with this pattern of comorbidity probably arising from shared risk factors including obesity, insulin resistance, metabolic syndrome, and an unfavourable body composition 130 .…”
Section: [H2] Medical Morbidity and Complications In Bedmentioning
confidence: 99%
“…This is especially relevant as binge-eating behaviours have been shown to worsen metabolic markers, including glycemic control 127 . Type 1 diabetes (T1D) as well as other autoimmune associated disorders were also more common in individuals with BED than referent controls 128 . In two pilot studies, 23% 129 to 28% 130 of people with nonalcoholic fatty liver disease (NAFLD) screened positive for BED, with this pattern of comorbidity probably arising from shared risk factors including obesity, insulin resistance, metabolic syndrome, and an unfavourable body composition 130 .…”
Section: [H2] Medical Morbidity and Complications In Bedmentioning
confidence: 99%
“…According to Larrañaga [72], the risk of disordered eating is greater in patients with T1DM compared to the general population due to multiple interacting factors related to DM and its treatment [19,20]. On the other hand, a recent meta-analysis [73] revealed that EDs are highly prevalent in T2DM, as both BED and BN appeared to increase the risk of T2DM.…”
Section: Characteristics Of Patients With Dm and On Tendenciesmentioning
confidence: 99%
“…According to a Danish and Swedish cohort study of more than 4,300,000 individuals [20], patients with T1DM exhibited a greater risk of having an ED diagnosis. Similar findings have also been confirmed in other populations [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Type 1 diabetes is a chronic auto-immune disease characterized by deterioration of insulin-producing beta cells in the pancreas, leading to insulin depletion and hyperglycemia [1]. Individuals with type 1 diabetes have a 2-threefold increased risk of disordered eating (DE) or eating disorders (ED) [2][3][4][5][6][7]. Coexisting type 1 diabetes and DE/ED is associated with impaired metabolic control and consequently an increased morbidity and mortality [8][9][10].…”
Section: Introductionmentioning
confidence: 99%